Re-Encountering Oneself. The MoltiMe Theatre Experience - Raccagni, Dalila; Sarzilla, Elena (INSTED: Interdisciplinary Studies in Education & Society, 2022)
A physical and mental space is needed so that the multiple identities that characterise the people of our time can meet and re-encounter each other. Today’s men and women, characterised by individualism and often described as indifferent (Bauman 1999, 2000), are sometimes tempted to shut themselves in their homes, becoming defensive and viewing interpersonal and community ties with suspicion. During this global pandemic, a time of re-appropriation and confrontation, people of different origins, neophytes of theatre, experienced the MoltiMe workshop, which was promoted by the Study and Training Centre on Human Mobility and Interculturality “Fileo”, situated in Bergamo (Italy). The workshop was devised as a narrative and relational necessity, but also as a chance to experiment with new expressive languages involving the word, the body, and its movement. The artistic potential is inherent in the spontaneity of the participants, who contaminate themselves with different languages, characterised by the resurfacing of the game aimed at investigating identity, otherness, and the connections between stories. This article presents this theatre course where different life stories intertwined. The experience allowed the meeting of multiple individual identities, rich in knowledge, feelings, and interiority, which enriched the group, offering a sense of belonging that created - in the group itself - a third dimension. In March 2020, the MoltiMe workshop continued to meet remotely and to address the issues of cultural diversity together with the theme of the pandemic, from which the performance “DI-Stanze Invisibili (tr. Invisible Di-Stances)” originated. The space that praised collateral beauty, activated in the diversified plurality that characterises the human, offered a wealth of knowledge, affections, and emotions, values ‘generated’ precisely in those existential passages often marked by bewilderment, isolation, and loss. At a time where people were tempted by selfish isolation, this experience instead offered - and continues to offer today thanks to a new experience of MoltiMe - the possibility of moments of re-appropriation of a personal time, which is enriched and filled with meaning in the encounter with otherness. An interpersonal encounter that was also an intercorporeal encounter. An experience that has been consolidated, and whose common thread in the last performance was language, which is mother, and traces the paths of ‘feeling at home’.